Strengthening community and stakeholder participation in the implementation of integrated vector management for malaria control in western Kenya: a case study - Peter N. Ng’ang’a (Malaria Journal, 2021)
Abstract Background Integrated vector management (IVM) is defined as a rational decision-making process for the optimal use of resources for vector control. The IVM approach is based on the premise that effective control of vectors and the diseases they transmit is not the sole preserve of the health sector. It requires the collaboration and participation of communities and other stakeholders in public and private sectors. Community participation is key to the success of IVM implementation at the local level. Case description The study was conducted in Nyabondo, a rural area of Kenya where malaria is endemic. The objective of the project was to promote adoption and sustainability of IVM and scale up IVM-related activities as well as increase community participation and partnership in malaria control through outreach, capacity-building and collaboration with other stakeholders in the area. Collaboration was pursued through forging partnership with various government departments and ministries, particularly the fisheries department, ministry of education, ministry of health, forestry department and the social services. In total, 33 community-based organizations working within the area were identified and their role documented. Through distribution of information, education and communication (IEC) materials alone, the project was able to reach 10,670 people using various social mobilization methods, such as convening of sensitization meetings—dubbed 'mosquito days'—mainly spearheaded by primary school pupils. A total of 23 local primary schools participated in creating awareness on malaria prevention and control during the project phase. The collaboration with other departments like fisheries led to stocking of more than 20 fishponds with a total of 18,000 fingerlings in the years 2017 and 2018. Fish ponds provided an opportunity for income generation to the community. In partnership with the county government health department, the project was able to re-train 40 CHVs on IVM and malaria case management in the area. Additionally, 40 fish farmers were re-trained on fish farming as part of income generating activity (IGA) while 10 CBOs made up of 509 members received both eucalyptus and Ocimum kilimandscharicum seedlings that were distributed to four CBOs composed of 152 members. Four primary schools made up of 113 health club members also received eucalyptus seedlings as part of IGA in addition to fish farming. In total, around 20,000 eucalyptus seedlings were distributed to the community as part of IGA initiatives. By the end of 2018, the project was able to reach 25,322 people in the community during its two-year advocacy and social mobilization initiatives. Conclusion Through advocacy and social mobilization, the IVM strategy improved inter-sectoral collaboration, enhanced capacity building and community participation. However, more IVM related activities are needed to effectively mobilize available resources and increase community participation in malaria control.